How can we incorporate nature connection into our work as learning developers? - Jodi Gregory (Journal of Learning Development in Higher Education, 2023)
This poster presents reflections on a year of facilitating regular outdoor ‘walk and talk’ activities embedded within a taught academic skills module. The aims were to foster connections between students, to deepen their sense of belonging, and to positively impact on their mental health by inviting them to spend time in local green spaces during timetabled class hours.